2021
DOI: 10.2217/fon-2021-0419
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of lymph node metastasis and pattern of repartition in patients with epithelial ovarian cancer

Abstract: Aim: To determine the rate, repartition and risk factors of lymph node (LN) metastasis in patients with epithelial ovarian cancer. Methods: We reviewed retrospectively the pathological and clinical data of 184 patients with epithelial ovarian cancer at a tertiary care center in Beirut, Lebanon. Results: 88% of patients received a pelvic and para-aortic lymphadenectomy. 70% of patients presented LN metastases at both pelvic and para-aortic levels, while isolated pelvic or para-aortic LN metastases were seen in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“… 70 75 Other researchers were interested in other types of cancers that were reviewed thoroughly along with their pathogenesis and possible treatment pathways. Other types of cancers that were of interest to LAU researchers were ovarian, 76 rectal, 77 cervical, 78 and gastroesophageal. 79 Moreover, different reviews provided insight into the potential of novel cancer therapies such as immunotherapy, CAR-T cells, and CDk-7 inhibitors in the treatment of oncological diseases.…”
Section: Resultsmentioning
confidence: 99%
“… 70 75 Other researchers were interested in other types of cancers that were reviewed thoroughly along with their pathogenesis and possible treatment pathways. Other types of cancers that were of interest to LAU researchers were ovarian, 76 rectal, 77 cervical, 78 and gastroesophageal. 79 Moreover, different reviews provided insight into the potential of novel cancer therapies such as immunotherapy, CAR-T cells, and CDk-7 inhibitors in the treatment of oncological diseases.…”
Section: Resultsmentioning
confidence: 99%
“…While HE4, CA724 and CEA levels were excluded in our clinical model. Previous studies have investigated the predictors of LNM in OC and concluded that high-grade serous tumors, positive peritoneal cytology, advanced clinical stage, interval surgery, and bilateral adnexal involvement can predict LNM in patients with OC [ 34 , 35 ]. This is consistent with our conclusion that peritoneal thickening on US images correlates with LNM.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that age, histology, grade, and CA125 level influenced the incidence of nodal metastasis. However, due to the limitations and small sample sizes of prior studies, little information exists about the lymph node status of patients with type I or type II disease [ 13 15 ]. Therefore, further studies are needed to explore the differences in lymph node status in OC patients with different types.…”
Section: Introductionmentioning
confidence: 99%